Mainstream Voters, Non-Voters and Populist Voters: What Sets Them Apart? - Cédric M. Koch; Carlos Meléndez; Cristóbal Rovira Kaltwasser (Political Studies, 2021)
Three different constituencies are becoming increasingly common across Western European electorates: mainstream voters, non-voters and populist voters. Despite their distinct behaviours in electoral politics, we have limited empirical knowledge about the characteristics that distinguish these three groups, given the typical underrepresentation of non-voters in surveys and the relative recency of large-scale research on populist voters. To address this gap, we analyse novel survey data from contemporary Germany that oversamples non-voters and includes a sizeable share of both populist radical left and populist radical right party supporters. Two main findings with broader implications stand out. First, populist voters resemble their mainstream counterparts in their expectations about democracy but correspond more closely to non-voters regarding (dis-)satisfaction with democracy. Second, non-voters and populist voters seem to reject mainstream democratic politics in distinct ways, throwing doubt on the (further) mobilization potential of abstainers for populist projects.
doi:10.25384/SAGE.16859061.v1
Keywords: 300; democracy; partisanship; populism; deprivation; non-voting